Leptin is related to body fat content in male distance runners - Hickey, M. S.; Considine, R. V.; Israel, R. G.; Mahar, T. L.; McCammon, M. R.; Tyndall, G. L.; Houmard, J. A.; Caro, J. F. (American Journal of Physiology, Endocrinology and Metabolism, 1996)
Leptin, the product of the ob gene, has been reported to be related to body fat in humans (Considine et al. N. Engl. J. Med. 334: 292, 1996). However, little is known about the physiology of this putative satiety signal in humans. The purpose of the present study was to determine whether leptin is related to body fat content in relatively lean endurance-trained adults. In addition, the effect of acute exercise on circulating leptin concentration was studied. Thirteen male runners, whose mean age, height, weight, %fat, and maximal oxygen consumption (VO2max) were 32.2 +/- 2.5 yr, 176.2 +/- 1.6 cm, 71.9 +/- 6.9 kg, 9.7 +/- 0.9%, and 62.9 +/- 2.2 ml.kg-1.min-1, respectively, were studied. Blood samples were obtained after an overnight fast and again immediately after the completion of a 20-mile run at 70% VO2max under controlled environmental conditions. Serum leptin was closely related to fat mass (r = 0.92) in the runners. Acute exercise had no detectable effect on serum leptin levels (PRE = 2.19 +/- 0.32 ng/ml, POST = 2.14 +/- 0.36 ng/ml). These data indicate that, even at a biological extreme of body fat, circulating leptin concentration is closely related to fat content. Furthermore, the data suggest that, in trained individuals with low leptin concentrations, acute exhaustive exercise has no immediate effect on circulating leptin concentration.